ORANGTUA DAN TEMAN BERMAIN TERHADAP PERKEMBANGAN SOSIAL ANAK (PARENTS AND PLAYING FRIENDS TOWARD CHILDREN SOCIAL DEVELOPMENT) - Sutrisno Sutrisno; Christiani Hutabarat (QUAERENS: Journal of Theology and Christianity Studies, 2019)
A positive relationship between parental assistance and playmates with children's social development which includes two dimensions, namely attitudes and behavior. Attitude is a tendency to react to people, institutions, or events both positively and negatively and behavior can be broadly defined, that is, everything that is done or experienced by a person and narrowly is behavior that includes reactions that can be observed in general or objectively observable. Hubungan yang positif antara pendampingan orangtua dan teman bermain dengan perkembangan sosial anak yang meliputi dua dimensi, yaitu sikap dan perilaku. Sikap adalah kecenderungan untuk mereaksi terhadap orang, institusi, atau kejadian baik secara positif maupun negatif dan perilaku dapat didefiniskan secara luas yaitu segala sesuatu yang dilakukan atau dialami seseorang dan secara sempit adalah tingkah laku yang mencakup reaksi yang dapat diamati secara umum atau objektif.